Introduction: A Democracy of Hope: The Stubborn Legacy of Struggle. - Dolgon, Corey (Theory in Action, 2010)
In an introduction to this issue, the writer pays tribute to Howard Zinn and Dennis Brutus, scholar activists who dedicated their life to changing the world. He recounts his experiences with Zinn and Brutus and provides an overview of the articles in the issue.